Answer:
The values for expression is h = - 2 and k = 5
Step-by-step explanation:
Given algebraic expression can be written as :
2 x³ - 10 x² + 11 x - 7 = ( x - 4 ) × ( 2 x² + h x + 3 ) + k
Now opening the bracket
Or, 2 x³ - 10 x² + 11 x - 7 = x × ( 2 x² + h x + 3 ) - 4 × ( 2 x² + h x + 3 ) + k
Or, 2 x³ - 10 x² + 11 x - 7 = 2 x³ + h x² + 3 x - 2 x² - 4 h x - 12 +k
Or , 2 x³ - 10 x² + 11 x - 7 = 2 x³ + ( h - 2 ) x² + ( 3 - 4 h ) x - 12 + k
Now, equating the equation both sides
I.e - 10 = ( h - 2 )
Or , h - 2 = - 10
I.e , h = - 10 + 2
∴ h = - 2
Again , 11 = ( 3 - 4 h )
or, 11 = 3 - 4 h
or, 11 - 3 = - 4 h
or, 8 = - 4 h
∴ h = ![\frac{-8}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B-8%7D%7B4%7D)
I.e h = - 2
Again
- 7 = - 12 + k
Or, k = - 7 + 12
∴ k = 5
Hence The values for expression is h = - 2 and k = 5 . Answer
Answer:
x=4 I dont know if you are trying to find the value is x
Step-by-step explanation:
Answer:
- <em>To solve these first swap x and y, solve for y and name it inverse function</em>
3. <u>y = -8x + 2</u>
- x = -8y + 2
- 8y = -x + 2
- y = -x/8 + 2/8
- y = -(18)x + 1/4
f⁻¹(x) = -(18)x + 1/4
-----------------------------------------
4.<u> y = (2/3)x - 5</u>
- x = (2/3)y - 5
- (2/3)y = x + 5
- y = (3/2)x + (3/2)5
- y = 1.5x + 7.5
f⁻¹(x) = 1.5x + 7.5
-----------------------------------------
5. <u>f(x) = 2x² - 6</u>
- x = 2y² - 6
- 2y² = x + 6
- y² = 1/2x + 3
- y =
![\sqrt{1/2x + 3}](https://tex.z-dn.net/?f=%5Csqrt%7B1%2F2x%20%2B%203%7D)
f⁻¹(x) = ![\sqrt{1/2x + 3}](https://tex.z-dn.net/?f=%5Csqrt%7B1%2F2x%20%2B%203%7D)
-----------------------------------------
6. <u>y = (x - 3)²</u>
- x = (y - 3)²
= y - 3- y = 3 +
![\sqrt{x}](https://tex.z-dn.net/?f=%5Csqrt%7Bx%7D)
f⁻¹(x) = 3 + ![\sqrt{x}](https://tex.z-dn.net/?f=%5Csqrt%7Bx%7D)
the first part isn't 90, it's 180.
the whole circle is 360, half of 360 is 180
an acute angle is any angle less than 90 degrees.